(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article discusses the role of biocompost in agriculture and the national economy, its importance in ensuring environmental sustainability, as well as its re-evaluation in the modern era as the “support of the century.”